UJI INOKULASI Fusarium sp UNTUK PRODUKSI GAHARU PADA BUDIDAYA A. Beccariana - iskandar, dudi; suhendra, ahmad (Badan Pengkajian dan Penerapan Teknologi, 2012)
Gaharu (Agarwood) is one of the most valuable of non-timber forest products (NTFPs) commodities in Indonesia that has an important role in economic and income for the community surrounding forest. However, the intensive exploitation and uncontrolled harvest capacity has brought those two potential species tends to decrease, and therefore gaharu is listed in the list of the CITES’ Appendix II. One of the solutions to deal with those cases researchers have been developing gaharu plantation as well technique to produce gaharu products through inoculation. Theaim of this study was to find the effectiveness of four different Fusarium sp from different locations in Indonesia (Parung/F1, Banjarmasin/F2, Jambi/F3 and Gorontalo/F4) in order to produce gaharu. These Fusarium were inoculated to 10 year’s old of A. Beccariana at Penajam, East Kalimantan. The result show that inoculant from Gorontalo (F4) gave the best result and the highest potential to the production of gaharu compare to other Fusarium sp.